Intraspecific niche partitioning in macrodetritivores enhances mixed leaf litter decomposition. (26th September 2019) - Fontana, Simone; Berg, Matty P.; Moretti, Marco
Abstract: In biodiversity and ecosystem functioning research, the consideration of intraspecific trait variation and multiple trophic levels – both largely overlooked so far – has been proposed as a promising step towards a consensus about causal relationships and mechanisms. Soil invertebrates contribute crucially to leaf litter decomposition and thus to the functioning of one of the most diverse ecosystem components on Earth. On the one hand, a positive effect of leaf litter diversity on decomposition was shown by several studies. On the other hand, at the interspecific level, differences in body size and feeding traits of consumers influence this process by interacting with leaf litter traits that define decomposability, such as nutrient content and physical properties. It is also known that the feeding niche of consumers can vary during their ontogeny as it depends on individual body size, metabolism and physiology. However, whether and how intraspecific trait variation of macrodetritivores contributes through niche partitioning to the positive effect of litter combinations on decomposition was never investigated. Here, we tested experimentally the effect of intraspecific body size differences in the common terrestrial isopod species Oniscus asellus on the decomposition of the two co‐occurring litter species Acer platanoides and Betula pendula . We hypothesized complementary resource use by two distinct isopod body size classes, leading to decreased competition and higher overall litter decomposition. In a full factorial design with all possible combinations of litter species and isopod body size classes, litter mixtures enhanced decomposition beyond the additive effect of each single species, especially in isopod mixed‐body size treatments. Our results suggest an interaction between litter and consumer diversity driving intraspecific feeding niche partitioning. Although the focus on a single detritivore species does not allow for generalizations, our results should stimulate the investigation of the mechanisms of biotic interactions among individual organisms. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.